An Operating Model to Operationalize the Modern Data Platform Using Distributed Data Mesh and Multi-Clouds - Mhala, Aniket (Digital Repository of Theses - SSBM Geneva, 2025)
The proliferation of data in terms of increasing volume, velocity, and variety of data have necessitated the development of advanced data platforms to support modern business needs. Distributed data mesh and multi-cloud architectures have emerged as promising approaches to address these challenges. However, the operationalization of these platforms remains a complex task, requiring a well-defined operating model to ensure efficient, scalable, and secure data management. This research aims to develop a comprehensive operating model that can guide organizations in the effective operationalization of modern data platforms utilizing distributed data mesh and multi-cloud architectures. The study seeks to address the critical question: How can organizations establish an effective operating model to operationalize their modern data platforms using distributed data mesh and multi-cloud architectures? The research explores the key components of an effective operating model, including data governance, data mesh principles, data as a product, data infrastructure, revised roles and responsibilities to adopt distributed data mesh across the enterprise in strategic and structured way. The scope of the research will be limited to the operational aspects of modern data platforms using data mesh, excluding strategic considerations such as data monetization and business intelligence.